ICT and change in teaching practices in Africa - (:unkn) unknown (My University, 2022)
This literature study gives the state of research on ICT in Africa. This research evokes the low level of penetration of ICT in African education systems and suggests possible solutions. They converge on the questions of reform of these systems, diverge on the unfavorable results of the presence of ICTE, and others neutral, support an in-depth pedagogical study and the technical tools available.
Keywords: African Research